Citraan dalam Puisi Daerah Sulawesi Selatan - Murmahyati Murmahyati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
This article aims to explain about imagery in South Sulawesi’s poems. The result to expect is story concerning the imagery poetry of South Sulawesi. Method of research used is descriptive method with sociological literature approach. Data were collected by using library research method. The researcher has found visual imagery, auditory imagery, olfactory imagery, tasting imagery, and motion imagery.